Coma [videorecording (DVD)] - Mukhametov, Rinalʹ, 1989-; Aksyonova, Lyubov, 1990-; Pampushnyĭ, Anton (MPI Media Group, 2020)
After a tragic accident, a young architect wakes up in a dystopian world. Here, the reality is made from the memories of people who have fallen into a comatose state. Cities, rivers, and the sky all flow in and out of each other fragmented and unstable just like our memories. The common laws of physics don't exist and nightmarish reapers roam the land spreading death.